Enhancing Community Welfare through Participatory Management of Village-Owned Enterprises: A Case Study in Pematang Serai Village, Langkat District - Daulay, Muhamad Toyib; Sanny, Annisa; Sari, Wahyu Indah; Riwanda, Febby (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the contribution of participatory management to improving community welfare through BUMDes in Pematang Serai Village, Langkat. Qualitative case studies are conducted through interviews and observations. The results show that participatory management is significant in empowering BUMDes and improving community welfare. Active community participation in the decision, planning, implementation, and evaluation of BUMDes has a positive impact on income, access to public services, and quality of life. This research makes an important contribution in understanding the role of participatory management in improving welfare through BUMDes. Relevant policy implications are outlined to support sustainable BUMDes and welfare in Pematang Serai Village.